2006
DOI: 10.1007/s00122-006-0315-1
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of the loci controlling oleic and linolenic acid contents and development of fad2 and fad3 allele-specific markers in canola (Brassica napus L.)

Abstract: The quality of canola oil is determined by its constituent fatty acids such as oleic acid (C18:1), linoleic acid (C18:2) and linolenic acid (C18:3). Most canola cultivars normally produce oil with about 55-65% oleic acid and 8-12% linolenic acid. High concentrations of linolenic acid lead to oil instability and off-type flavor, while high levels of oleic acid increase oxidative stability and nutritional value of oil. Therefore, development of canola cultivars with increased oleic acid and reduced linolenic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
136
3
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(150 citation statements)
references
References 32 publications
6
136
3
1
Order By: Relevance
“…The traits controlled by multiple genes such as palm oil composition can be deciphered using modern DNA marker technologies to implement a marker-assisted selection (MAS) for more desirable fatty acid composition, as it is already done for other oil crops like oilseed rape (Brassica napus) (Hu et al 1999(Hu et al , 2006Smooker et al 2011) soybean (Glycine max (L.) Merr.) (Wilson et al 2001;Monteros et al 2008;Ha et al 2010;Li et al 2011;Chen et al 2012) and olive (Olea europaea L.) (Poghosyan et al 1999;Hernández et al 2005;Banilas et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The traits controlled by multiple genes such as palm oil composition can be deciphered using modern DNA marker technologies to implement a marker-assisted selection (MAS) for more desirable fatty acid composition, as it is already done for other oil crops like oilseed rape (Brassica napus) (Hu et al 1999(Hu et al , 2006Smooker et al 2011) soybean (Glycine max (L.) Merr.) (Wilson et al 2001;Monteros et al 2008;Ha et al 2010;Li et al 2011;Chen et al 2012) and olive (Olea europaea L.) (Poghosyan et al 1999;Hernández et al 2005;Banilas et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Linkage analysis with 183 doubled haploid lines derived from the cross of Quantum and DMS100 indicated that this allele-specific marker was significantly correlated to low C18:3. A high-throughput Invader ® assay detecting the SNP generated from the fad3c gene mutation clearly differentiated the homozygous mutant, homozygous wild-type and heterozygous genotypes, thus allowing specific selection of the fad3c alleles conferring low C18:3 content (Hu et al 2006).The molecular characterization of mutations in splicing site sequences in Arabidopsis provides valuable information on plant pre-mRNA splicing. As in other organisms, plant genes contain highly conserved 5Ј splice site (exon/intron junction-AG/GTAAG) and 3Ј splice site (intron/exon junction-TGCAG/G).…”
mentioning
confidence: 99%
“…Two fad3 genes ( fad3a and fad3c) were reported to control linolenic content in Brassica napus, with fad3a located on linkage group N4 and fad3c on N14 (Barret et al 1999;Brunel et al 1999;Hu et al 2006). The high level of linolenic acid in canola oil is undesirable because linolenic acid is highly unsaturated and easily oxidized to cause off-flavor and rancidity of the oil, thus resulting in a shortened shelf life.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…oxidative stability, low-temperature operability, lubricity, corrosiveness). Selection for breeding and genetic engineering approaches resulting in elevated oleic acid levels have been reported in many oilseed crops [96][97][98]. Conventional soybean lines with 80% oleic acid accompanied by a corresponding decrease in linoleic acid were obtained based on the contribution of only two genes (FAD2-1A and FAD2-1B) [99].…”
Section: Improvement Of Biodiesel Feedstocksmentioning
confidence: 99%